Classification, identification, and reservoir characteristics of intermediate mafic lava flows: a case study in Dongling area, Songliao Basin - Yue, Qingyou; Wang, Baozhu; Ren, Xianjun; Cang, Zhengyi; Han, Jiaoyan; Li, Cunlei; Zhao, Ranlei; Wang, Haidong (Frontiers in Earth Science, 2023)
Intermediate mafic lava is a special oil and gas reservoir. While its internal structure is an important factor affecting the reservoir properties, the identification of facies and understanding of the relationship between facies architecture and reservoir are limited. This study evaluated the intermediate mafic lava flows of the Yingcheng Formation in the Dongling area of Songliao Basin by analyzing drilling cores, corresponding thin sections, and scanning electron microscope (SEM) images, as well as well-logging and seismic attributes. We also performed helium gas experiments and high-pressure mercury intrusion (HPMI) analysis to assess the physical properties and pore structure of the reservoir, respectively. The results showed that intermediate mafic lava flows develop tabular lava flow, compound lava flow, and hyaloclastite. Three facies showed present diverse well-logging and seismic responses. The intermediate mafic lava facies architecture was divided into crater-proximal facies (CF-PF), medial facies (MF), and distal facies (DF), which were characterized by their vesicles and joints and could be identified through their seismic attributes. The reservoir spaces including vesicles, amygdale inner pores, joint fissures, and dissolution pores predominantly showed oil and gas accumulation. The results of the tests of the reservoir’s physical properties showed that the reservoir quality was best in the CF-PF, which is the main target of oil and gas exploration.